(untitled) (Studia theodisca, 2020)
Antigone’s myth seems to be one of the few ancient ones to have become in every way a myth in the modern sense: a reference image functioning as a means of rapid identification and as a flag of shared values. Antigone ended up becoming for us the myth of the Human against the political dimension, which is now being instinctively reduced to the constitutive violence of all power. By first concentrating on some critical moments of Sophocles’ version, and then on some often neglected aspects of the version Brecht wrote in 1947, the following notes attempt to deconstruct this both on stage and in its reception within the dominant social imaginary. Although Brecht’s Antigone is usually staged in line with this imaginary, it seems to offer, rather more than a correction or an update of Sophocles’ text, an already critical counterpart to our contemporary reception of its underlying myth.